Ion-pairing liquid chromatographic method determination of ketoconazole and stress degradation in pharmaceutical formulations with fluorescence detection - Wisanu Thongchai (Universidade de São Paulo, 2020)
Ion-pairing liquid chromatographic method was validated for determination of ketoconazole in shampoo and cream samples as per ICH guidelines. The chromatographic conditions were carried out in the isocratic mode using a mixture of methanol and 8 mM sodium dodecyl sulfate (pH 5.5) in a ratio of 45:55 v/v %, as mobile phase. The flow rate was set at 1.0 mL min-1. Chromolith RP-18e (100×4.6 mm) was used as the analytical column with a fluorescence detection at an excitation wavelength of 260 nm and an emission wavelength of 375 nm. The average percentage recovery of shampoo A, shampoo B, shampoo C, cream A and cream B were 99.88, 97.06, 99.58, 96.77 and 97.26, respectively. The limit of detection was 0.12 mg L-1. The drug decomposition under acid degradation, base degradation and oxidative degradation were found to be in the range of 91.63-94.70% indicating that the drug is resistant towards acidic conditions. The drug decomposition under thermal condition and photolysis condition were found to be in the range of 69.05-87.15% and 47.31-66.83% respectively, indicating that the drug decomposition is more sensitive under photolysis conditions. This method is suitable for the quality control of ketoconazole in commercial shampoo and creams.